Foreign exchange deal allocation - Pillay, Dayanithi (My University, 2011)
This study sets out to identify the criteria that multi-banked corporate customers operating in South Africa use to decide which bank to allocate each foreign exchange deal to. The foreign exchange market is highly competitive, in order to retain and grow market share the banks operating in this environment must identify what criteria their clients use when deciding which banks to allocate their foreign exchange deals to. This study focuses on the multi-banked corporate segment operating in South Africa. Based on the literature review the proposition derived was: The criteria that influence foreign exchange deal allocation decisions include: - - Trusted advisor / Relationship based on trust - Competitive prices for products and services - Quality and range of services and products - Accommodation of credit needs A qualitative research method, utilizing 16 in-depth interviews, was employed for this study. The research instrument was a semi-structured questionnaire with mostly open-ended questions. Conceptual themes were drawn from the data and illustrated using the principles of Concept maps. The South African respondents identified “Processing efficiency” as being important to the deal allocation decision. The proposition was therefore partially accepted.
MBA - WBS
Keywords: Foreign exchange; Banks and banking